Cancer Mortality in Older Mexican Individuals (2000 – 2010) - González Santiago, Omar; Castillo Guzmán, Sandra; Palacios Ríos, Dionicio; Ramírez Cabrera, Mónica Azucena (2014)
Objective: Given the trends in aging worldwide, in Mexico, we determined trends in adjusted mortality rates due to cancer and 11 cancer subtypes in older individuals (>65 years) from 2000 to 2010. Methods: For this retrospective study, we collected data on mortality due to cancer from the registries of the National Institute of Statistics and Geography. Adjusted rates were calculated with a direct method based on the world standard population. Trend analysis was performed with a linear regression of the natural logarithm of the adjusted rate, and trends were evaluated with the Student´s t test. Results: During the studied period, the cancer mortality rates significantly declined from 630.21 to 573.03 (per 100,000 inhabitants) in the overall population. Similar declines were observed in women (from 548.81 to 490.09) and men (from 726.03 to 672.94). Significant declines in mortality rates were observed across several cancer subtypes, including esophageal, gastric, colorectal-anal, liver-biliary, pancreatic, and tracheal-bronchial-lung cancers. Significant increases in mortality rates were observed in colorectal and breast cancer, but no changes were observed in mortality rates due to prostate, ovarian, bladder, and non-Hodgkin lymphoma cancers. Conclusion: Mortality due to cancer in older Mexicans was lower than that observed in developed countries, and it significantly declined over the study period. Men had higher mortality rates than women. The highest mortality rates were due to breast and prostate cancer subtypes in older individuals.